Enhanced Hydrogen Peroxide Sensing Based on Tetraruthenated Porphyrins/Nafion/Glassy Carbon‐modified Electrodes via Incorporating of Carbon Nanotubes. Issue 12 (14th July 2015) - Calfumán, Karla; Quezada, Diego; Isaacs, Mauricio; Bollo, Soledad
Abstract: The incorporation of carbon nanotubes to a Nafion/tetraruthenated cobalt porphyrin/ glassy carbon electrode (GC/Nf/CoTRP vs GC/Nf/CNTCoTRP) enhanced the amperometric determination of hydrogen peroxide. Both electrodes produced a decrease in the overpotential required for the hydrogen peroxide oxidation in about 100 mV compared to glassy carbon under the same experimental conditions. Nevertheless, for GC/Nf/CNT/CoTRP, the increase in the current is remarkable. The GC/Nf/CoTRP modified electrode gave no significant analitycal signal for hydrogen peroxide reduction. Moreover, a great increase in current is observed with GC/Nf/CNT/CoTRP at −150mV which suggests a significant increase in the sensitivity of the modified electrode. Scanning electrochemical microscopy (SECM) revealed an enhancement in the electroactivity of the GC/Nf/CNT/CoTRP modified electrode. This fact has been explained in terms of enhanced homogeneity of the electrodic surface as a consecuence of better dispersibility of CNT‐CoTRP produced by a Nafion polyelectrolyte. Abstract :